Technical and instrumentational foundations of PET/MRI. Issue 94 (September 2017) - Rausch, Ivo; Quick, Harald H.; Cal-Gonzalez, Jacobo; Sattler, Bernhard; Boellaard, Ronald; Beyer, Thomas
Highlights: An introduction to PET and MRI is given. MRI based attenuation correction in whole-body PET/MRI is discussed. An introduction in advanced imaging technics in PET/MRI is given. Abstract: This paper highlights the origins of combined positron emission tomography (PET) and magnetic resonance imaging (MRI) whole-body systems that were first introduced for applications in humans in 2010. This text first covers basic aspects of each imaging modality before describing the technical and methodological challenges of combining PET and MRI within a single system. After several years of development, combined and even fully-integrated PET/MRI systems have become available and made their way into the clinic. This multi-modality imaging system lends itself to the advanced exploration of diseases to support personalized medicine in a long run. To that extent, this paper provides an introduction to PET/MRI methodology and important technical solutions.